Online optical shop management system - Chua, Poh Wee (2010)
This thesis in title "Online Optical Shop Management System" which is a shop management system to manage optical shop business and it is implemented with inventory management. There are five (5) main modules in this system, which are log in and registration, inventoi r management, transaction management, staff management, and financial management. The problem statement of this thesis are the current management system is filing system to record the sales, customers, staff,stock record and there are no well inventory management is using and the record of the stock was not complete, only depend on the invoice they received as stock record. There are two (2) objectives of this thesis, which are to computerize the shop management system from manual system and to implement an inventory management system to manage the stock of the optical shop. This thesis is discussed on how the online optical shop management system to be implemented,the tools and programming languages used, and the resources needed in developing this system. Model Software Development Life Cycle (SDLC) is used to develop this project. There are seven (7) phases which are identifying system requirements,system planning, system analysis, system design, system implementation, system testing and system maintenance. The strength of OOSMS is implemented with the well inventory management to manipulate the inventory of the shop. Low level of stock quantities will be notified to the user automatically. This thesis had been successfully completed and the system is successfully developed and function able.